The Relationship Between Stigma and Mood in College Students with Disabilities - Knox, Caroline (East Carolina University, 2023)
Approximately 20% of college students report having a disability, including physical (visible), cognitive, and psychiatric (non-visible) disability types. Decades of research have documented negative stereotyping and perceived discrimination against students with disabilities (e.g., DaDeppo, 2009; Lyman et al., 2016). To understand the negative effects stigma may have, it is important to consider how stigma might influence one’s feelings and intent to persist with college. It is also important to find factors that may mitigate negative effects, such as one’s ability to bounce back from stress (resilience). This study explored correlations between the perceived stigma of students with various types of disabilities, their resilience, affect, and intent to persist from one semester to the next. It was hypothesized that college students with disabilities with higher levels of stigma would have a higher negative effect and lower intent to persist, but their level of resilience would moderate this. Using established measures, college students with different disability types, including those who receive accommodations and those who don’t, were surveyed. The participants included students in the STEPP program and students who use Disability Support Services at ECU. Results found that, as perceived stigma increases, negative affect increases. Individuals with disabilities who experienced higher stigma reported lower resiliency. Although resiliency and stigma did have an impact on affect independently, resiliency did not act as a moderator, or buffer, between stigma and affect. Findings are consistent with previous qualitative studies suggesting that more mental health resources for college students with disabilities should be considered. Study limitations and directions for future research are presented.
Keywords: disabilities, stigma, mood